Low Power Implementation of QRS Detection System (International Journal of Innovative Research in Computer Science & Technology, 2023)
This paper proposes a modification of the  pre-processing stage of the Pan-Tompkins algorithm. In  this paper, the fractional order differentiator now stands in  for the integer order differentiator. Since the gain of the  fractional order differentiator is lesser than its integer order  counterpart, the amplification of the high frequency noise  is reduced thus making the design robust to noise.  Moreover, all the circuits in this design have been  implemented using low-power design techniques so that  the system can work with extremely low power  consumption. The achievement of the advanced design has  been validated by simulations carried out in the HSPICE  EDA tool using the TMSC CMOS 130nm process.
Keywords: QRS; Pan Tompkins Algorithm; Fractional Order differentiator; ECG Signal; Bandpass filter